PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. ISS INDONESIA PENEMPATAN GRAND SLIPI TOWER JAKARTA BARAT - Darmadi Darmadi; N. Lilis Suryani; Iman Syatoto (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This research was conducted with the aim of knowing the effect of work motivation and discipline on employee performance at PT. ISS Indonesia Placement for Grand Slipi Tower, West Jakarta. This study uses an associative descriptive method with a quantitative approach used to test population parameters through statistics. The population in this study are employees who work at PT. ISS Indonesia Placement of Grand Slipi Tower West Jakarta as many as 60 people using saturated sampling technique. Data collection techniques were carried out using primary data collection methods (observation and questionnaires), secondary data and data analysis techniques using validity tests, reliability tests, normality tests, multiple linear regression analysis tests, and determination test. The results showed that the coefficient of determination of the motivation variable was 55.7% with a correlation coefficient of 0.746, which means that motivation has a strong relationship to employee performance. The hypothesis test obtained tcount > ttable (4.365 > 2.003), this was also reinforced by a significance value of 0.000 <0.05 Then H0 was rejected and H1 was accepted, meaning that there is a positive and significant influence between motivation on employee performance. The coefficient of determination for the work discipline variable is 58.7% with a correlation coefficient value of 0.766, which means that work discipline has a strong relationship to employee performance. Hypothesis testing obtained tcount > ttable (4.937 > 2.003), this was also reinforced by a significance value of 0.000 <0.05. Then H0 is rejected and H1 is accepted, meaning that there is a positive and significant influence between work discipline on employee performance. Motivation and work discipline simultaneously have a positive and significant effect on employee performance with the multiple linear regression equation Y = -5.443 + 0.524X1 + 0.550X2 and the value of the coefficient of determination contributes 69.5% while the remaining 30.5% is influenced by other factors that not examined in this study. The hypothesis test obtained the value of Fcount > Ftable (61.384 > 3.16), this is reinforced by a significance value of 0.000 <0.05. Then H0 is rejected and H1 is accepted, meaning that there is a positive and significant influence between motivation and work discipline simultaneously (simultaneously) on the performance of employees of PT. ISS Indonesia Placement for Grand Slipi Tower, West Jakarta.